2016
DOI: 10.1152/japplphysiol.00885.2015
|View full text |Cite
|
Sign up to set email alerts
|

Home-based aerobic exercise training improves skeletal muscle oxidative metabolism in patients with metabolic myopathies

Abstract: Aerobic training can be effective in patients with mitochondrial myopathies (MM) and McArdle's disease (McA). The aim of the study was to use noninvasive functional evaluation methods, specifically aimed at skeletal muscle oxidative metabolism, to evaluate the effects of an aerobic exercise training (cycle ergometer, 12 wk, 4 days/wk, ∼65-70% of maximal heart rate) in 6 MM and 7 McA. Oxygen uptake and skeletal muscle vastus lateralis fractional O2 extraction by near-infrared spectroscopy were assessed during i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 46 publications
2
70
0
Order By: Relevance
“…The dynamic profiles of ∆[deoxy(Hb + Mb)] during the first 2 min of unloaded knee extension were analysed to evaluate parameters related to the intramuscular matching between O 2 delivery and O 2 consumption in the vastus lateralis muscle (Porcelli et al . , , ; Grassi & Quaresima, ; Salvadego et al . ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The dynamic profiles of ∆[deoxy(Hb + Mb)] during the first 2 min of unloaded knee extension were analysed to evaluate parameters related to the intramuscular matching between O 2 delivery and O 2 consumption in the vastus lateralis muscle (Porcelli et al . , , ; Grassi & Quaresima, ; Salvadego et al . ).…”
Section: Discussionmentioning
confidence: 98%
“…), as well as in patients with metabolic myopathies (Porcelli et al . , ). According to another possibility, the transient overshoot in O 2 extraction may be the consequence of an accumulation of blood in skeletal muscle at rest, which has been hypothesized to occur during bed rest (Rittweger et al .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that aerobic training decreases serum CK activity in MCD patients [7]. In addition, it has been reported that aerobic training program significantly attenuated the impairment of skeletal muscle oxidative metabolism and improved variables associated with exercise tolerance [11], [59]. In contrast, deconditioning [60], immobilization [61] or age-related changes (decline of physical activity) [19], [62], lead to higher oxidative stress which may be very similar to MCD patients where the level of physical activity is low.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have recently established PJP as a novel quantitative measurement shown to classify levels of ambulatory ability for patients with rare neuromuscular disorders, including mitochondrial disease [ 19 ]. The benefits of exercise in patients with mitochondrial disease has also been well established [ 21 ], with evidence for improved oxidative metabolism [ 22 ], mitochondrial proliferation [ 23 ], and gene-shifting from the recruitment of satellite cells [ 24 ] to name just a few mechanisms. SAVT can improve truncal strength [ 25 ], improve muscle function from exercise induced muscle damage [ 26 ], and attenuate the effects of aging on skeletal muscle [ 26 ].…”
Section: Discussionmentioning
confidence: 99%